Analisis Efisiensi Pemasaran Pala di Kecamatan Tapaktuan Kabupaten Aceh Selatan - Sofyan Sofyan; Elvira Iskandar; Faradila Febriani (Universitas Teuku Umar, 2017)
The nutmeg plant known as spice plants that has economic value. South Aceh district is an area of nutmeg production centers in Aceh. The purpose of this study was to determine the type of marketing channels, margin and marketing efficiency nutmeg in Tapak Tuan Sub District. This research was conducted by survey. The analytical method used is quantitative descriptive method by analysis of marketing margin and efficiency. The results showed that: (1) Channel marketing of meat nutmeg using zero channel level, while the nutmeg seed marketing channels using the channel one and two levels; (2) marketing margin nutmeg to consumers in Type I of Rp.20.500 per kg and the Type II amounted Rp.21.000 per kg, while the marketing channel nutmeg to refiners in Type I Rp. 95 900 per kg and the Type II Rp. 96 400; (3) The efficiency of marketing nutmeg to consumers in Type I 53.94% and the Type II 55.26%, while nutmeg to refiners at 84.65%of Type I and Type II at 85%.